Variation of the breast cancer susceptibility marker, rs4245739, is associated with differential miRNA binding and MDM4 expression - Sumadi Lukman Anwar; Angel Carlos-Roman; Wahyu Wulaningsih; Johnathan Watkins (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
A polymorphism, rs4245739, has been associated with susceptibility of several cancers including ER-negative breast cancer. Rs4245739 is located at the 3’UTR of MDM4 gene, an oncogene that negatively regulates p53. The polymorphism has been associated with binding changes of miR-191. We studied, the influence of SNP rs4245739 to the binding of microRNAs, expression of microRNAs and MDM4. Using FindTar software, we detected potential microRNAs affected by the SNP-flanking sequence. We then used RNA sequencing data from ER-negative breast cancer to compare expression of miR-184, miR-191, miR-193a, miR-378, and MDM4 in different genotypes. Comparison of ER-negative patients with and without expression of miR-191 as well as profile microRNAs (miR-184, miR-191, miR-193a and miR-378 altogether) can differentiate expression of MDM4between different alleles. In addition, the number of lymphatic nodes affected in the individuals was also found to be significantly reduced in the risk group obtained by the miRNA profile method. We show our methods especially miRNA profile approach, are able to obtain new molecular and clinical features related to the rs4245739 SNP, a variant located in the 3’UTR of MDM4 gene and known to appear in different types of cancer. Keywords: ER negative breast cancer, rs4245739, microRNA, MDM4, p53